Corpus analysis of conjunctions : Arabic learners' difficulties with collocations - Hassan, Haslina (2011)
This paper investigated Arabic majors use of conjunctions in essays produced for Computer Applications for Language Studies course offered by the Department of Arabic Language and Literature of the International Islamic University Malaysia (IIUM). The essays were submitted through the university’s Learning Management System (LMS). It serves as a corpus for this study. SketchEngine was employed to track the frequency of conjunctions used by the students. However, SketchEngine was limited in its applications in that it is unable to detect the collocations for a number of conjunctions. Hence, Excel had to be used with Sketch Engine to get a more reliable data for this study. Findings revealed that there are a number of favourite conjunctions among the learners. The main problem with its usage lies in the use of collocations. The analysis revealed that out of more than 83 conjunctions available only six were commonly used by the students. Their usage, however, was not necessarily correct. There seemed to be a confusion in the application of these conjunctions, particularly those which carry similar meanings. The contexts of their applications are different. Mother tongue interference could be the reason for the confusion since the direct translation of the word can be used in the same context. This study highlighted the need to focus on these errors when teaching Arabic to second or foreign language learners.